Case Report: A BRCA2 Mutation Identified Through Next-Generation Sequencing in a Birt–Hogg–Dubè Syndrome Family - Bandini, Erika; Cangini, Ilaria; Arcangeli, Valentina; Ravegnani, Mila; Andreotti, Virginia; Prisinzano, Giovanna; Pastorino, Lorenza; Martinelli, Giovanni; Falcini, Fabio; Calistri, Daniele; Zampiga, Valentina; Danesi, Rita (Frontiers in Oncology, 2022)
Birt-Hogg-Dubé syndrome (BHDS) is a rare autosomal dominant inherited disorder caused by a mutation in the folliculin (FLCN) gene, transmitted via germline autosomal dominant pattern. Patients with this syndrome have an increased susceptibility to renal cell carcinoma, lung cysts, spontaneous pneumothorax, benign skin hamartomas, and its diagnosis is not easy and consequently underestimated. Several mutations have been identified in the FLCN gene, among which the majority of alterations are frameshift (insertion/deletion), nonsense or splice site mutations that generally produce unfunctional truncated FLCN proteins. Our aim is that of presenting a case of a BHDS family, whose proband is a 56 years old patient experienced multiple disorders, to whom, in addition to show a FLCN genetic mutation, was also identified a pathogenic variant in BRCA2 gene. Our further purpose is to emphasize the importance of Next Generation Sequencing (NGS) approach to identify potential multiple germline mutations in complex and rare oncologic disorders, allowing strict and more targeted cancer screening programs.